Application of Flipped Classroom on Students' Learning Motivation on Human Excretion System Material - Rahmat Putra; Khairil Khairil; Ismul Huda; Hafnati Rahmatan; Wiwit Artika (Jurnal Penelitian Pendidikan IPA, 2022)
The low motivation of students is one of the problems in learning. Motivation is an impulse that causes an action to occur in order to achieve a goal. Evidence of the low level of understanding of students is seen from the average value of 32.26% which is still below the minimum completeness criteria. One of the efforts that can be done in solving motivational problems is to apply the flipped classroom model. This study aims to determine the effect of the application of the flipped classroom model on the motivation of students on the human excretory system material carried out in 2 high schools, namely SMA Negeri 1 Tapaktuan and SMA Negeri 1 Sawang. This research is quantitative through a Quasi-Experimental approach with a Non-randomized control group design, posttest-only design. The research sample was 195 students who were divided into two groups, namely 97 control groups and 98 experimental groups. The instrument used in this study was an ARCS motivation questionnaire. Motivation data were analyzed using the Anova test. The results of research on motivation show the value of Asymp Sig (0.00) < (0.05) which means that the application of the flipped classroom model has a significant effect on motivation. The conclusion in this study is that the application of the flipped classroom model has a significant effect on learning outcomes and student motivation